LANGUAGE AND IDENTITY: CULTURAL METAPHORS IN UZBEK AND ENGLISH PROVERBS (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article investigates how cultural metaphors embedded in proverbs reflect the interplay between language and identity in Uzbek and English societies. Proverbs serve not only as linguistic expressions but also as carriers of cultural norms, values, and worldviews. Through comparative analysis, the paper highlights similarities and differences in metaphorical conceptualizations related to family, honor, wisdom, and fate. Findings suggest that while some metaphorical patterns are universal, many are deeply rooted in each culture’s unique historical and social experience.